Anti-Staphylococcal Activity of Ligilactobacillus animalis SWLA-1 and Its Supernatant against Multidrug-Resistant Staphylococcus pseudintermedius in Novel Rat Model of Acute Osteomyelitis - Sung-Yong Park; Hong-Jae Lee; Hyo-Sung Kim; Dong-Hwi Kim; Sang-Won Lee; Hun-Young Yoon (MDPI AG, 2023)
Osteomyelitis caused by staphylococcal infection is a serious complication of orthopedic surgery. Staphylococcus pseudintermedius is the main causative agent of osteomyelitis in veterinary medicine. Methicillin-resistant S. pseudintermedius (MRSP) has been reported in companion animals, especially dogs. Multidrug-resistant S. pseudintermedius is an emerging pathogen and has acquired antibiotic resistance against various commercial antimicrobial agents. New antimicrobial compounds are urgently needed to address antibiotic resistance, and the development of novel agents has become an international research hotspot in recent decades. Antimicrobial compounds derived from probiotics, such as bacteriocins, are promising alternatives to classical antibiotics. In this study, the antibacterial activities of Ligilactobacillus animalis SWLA-1 and its concentrated cell-free supernatant (CCFS) were evaluated in vitro and in vivo. The CCFS of this bacterium showed no toxicity against osteoblast and myoblast cells in vitro, while significantly inhibiting the multidrug-resistant S. pseudintermedius KUVM1701GC strain in a newly established rat model. The CCFS significantly inhibited multidrug-resistant staphylococci both in vitro and in vivo. This suggests that CCFS derived from L. animalis SWLA-1 has potential as an alternative to classic antibiotics for staphylococcal infections in dogs.